2018
DOI: 10.1248/bpb.b17-00798
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Key Factors for Optimizing the <i>in Vivo</i> Oral Delivery of Insulin by Using a Noncovalent Strategy with Cell-Penetrating Peptides

Abstract: This present study aimed to determine the optimal oral insulin delivery conditions that would maximize the utility of cell-penetrating peptides (CPPs) by using a noncovalent strategy. We first compared the effectiveness of two potential CPPs, penetratin and its analog PenetraMax, as absorption enhancers for insulin. The combined effect was evaluated under in vivo oral administration conditions. Both D-forms of CPPs were highly effective for increasing the oral absorption of insulin, and D-PenetraMax showed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
2
7
1
Order By: Relevance
“…CPPs such as penetratin and its analog, PentraMax TM , continue to be researched for oral peptide delivery. There is evidence that these CPPs act by altering membrane barrier integrity [30], endocytosis [30], and physical complexation [31]. Although a few CPPs have progressed to clinical evaluation, the majority relate to the intracellular delivery of small molecules and not to oral delivery of macromolecules [32].…”
Section: Permeation Enhancer (Pe) Categoriesmentioning
confidence: 99%
“…CPPs such as penetratin and its analog, PentraMax TM , continue to be researched for oral peptide delivery. There is evidence that these CPPs act by altering membrane barrier integrity [30], endocytosis [30], and physical complexation [31]. Although a few CPPs have progressed to clinical evaluation, the majority relate to the intracellular delivery of small molecules and not to oral delivery of macromolecules [32].…”
Section: Permeation Enhancer (Pe) Categoriesmentioning
confidence: 99%
“…However, that study also concluded that the effect of D-penetratin was superior to the effect of the L-form, which do not comply with our results. 20 Another study by the same research group reported that the stereochemistry effect depended on the region of rat intestines investigated; 21 direct correlations may thus not be evident between different methodologies. This difference in the effect of stereochemistry for the different peptides suggests that the grouping of residues and the positioning of the cationic residues in the amino acid sequence influence the carrier peptide efficacy.…”
Section: ■ Discussionmentioning
confidence: 99%
“…25 The insulin−carrier peptide interactions did not, however, depend on the stereochemistry as observed from the SAXS investigation, consistent with a study of insulin− penetratin interactions using surface plasmon resonance. 20 Other factors might therefore influence the carrier peptidemediated insulin permeation, which account for the stereochemistry-dependent enhancement of insulin permeation by Dpenetratin and D-penetramax (Figure 3C).…”
Section: ■ Discussionmentioning
confidence: 99%
“…The low molecular weight protamine (LMWP) with a sequence of VSRRRRRRGGRRRRC is the one of CPPs, which can increase the intestinal cell membrane permeability and oral relative bioavailability of exenatide-Zn 2+ by 29-fold 213 . Both Penetratin® and its analog PenetraMax® exerted absorption enhanced ability for oral insulin in D-form by non-covalent approach; but there is no synergistic effect observed when using the combination of these two CPPs 214 . Although CPPs have exerted excellent capacity in improving membrane permeability, they have not yet been validated in the clinic studies of oral delivery of peptides due to complex GI environment.…”
Section: Current Strategies Towards Enhancement Of the Oral Absorption Of Ppsmentioning
confidence: 99%